[4 + 2] Cycloaddition of trifluoromethyl ketimines with 2-alkenyl azaarenes through selective C–F bond cleavage of CF3. Issue 16 (15th June 2021) - Fu, Yiwei; Qin, Cong; Zhang, Zhiqiang; Shi, Haoyu; Zhao, Jianbo; Gong, Xueqing; Shi, Lei; Li, Hao
Abstract : A transition-metal-free [4 + 2] cycloaddition of trifluoromethyl ketimines with 2-alkenyl azaarenes through selective C–F bond cleavage of CF3 has been developed to afford cis -tetrahydroxypyridine products in moderate yields under mild conditions. Abstract : We have developed a new [4 + 2] cycloaddition of trifluoromethyl ketimines with 2-alkenyl azaarenes through selective C–F bond cleavage of CF3 . The reactions are promoted by 2, 2, 6, 6-tetramethylpiperidine (TMP) under mild conditions to give cis -tetrahydropyridine products in moderate yields. Density functional theory (DFT) calculations reveal that the in situ formed ( E )- N -(2, 2-difluoro-1-phenylvinyl)-1-phenylmethanimine is the key intermediate for the formation of cis -tetrahydropyridine products which have the lowest energy among the four possible products.